2017
DOI: 10.1186/s12944-016-0396-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of fatty acids on ICSI outcomes: a prospective cohort study

Abstract: BackgroundOur objective was to determine the effect of fatty acids (FAs) in serum and follicular fluid (FF) on fertilization and intracytoplasmic sperm injection (ICSI) outcomes.MethodsOne hundred five women aged 18–38 years undergoing ICSI were recruited in this prospective cohort study. oocyte and emberyo quality was morphologically assessed. FAs in serum and FF were analyzed, using gas chromatography–mass spectrometry (GC-MS).ResultsThe mean number of mature oocytes was associated with serum levels of oleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
5
48
3
1
Order By: Relevance
“…The EARTH study reported that for every 1% increase in serum long-chain u-3 PUFA levels, the probability of clinical pregnancy and live birth increased by 8% (102). In another study, serum levels of eicosapentaenoic acid (a long-chain u-3 PUFA) were significantly higher in pregnant than in nonpregnant patients (103). In addition, higher preconception u-3 PUFA intake was associated with better embryo morphology, despite being inversely associated with response to ovarian stimulation (104).…”
Section: Fatty Acidsmentioning
confidence: 98%
“…The EARTH study reported that for every 1% increase in serum long-chain u-3 PUFA levels, the probability of clinical pregnancy and live birth increased by 8% (102). In another study, serum levels of eicosapentaenoic acid (a long-chain u-3 PUFA) were significantly higher in pregnant than in nonpregnant patients (103). In addition, higher preconception u-3 PUFA intake was associated with better embryo morphology, despite being inversely associated with response to ovarian stimulation (104).…”
Section: Fatty Acidsmentioning
confidence: 98%
“…No correlation between omega-3 PUFA index and IVF outcomes, such as number of oocytes retrieved, embryo grade or clinical pregnancy, was found in another small study (n = 60) (Eskew et al, 2017). Mirabi et al (2017) measured serum and follicular fluid level of fatty acids in 105 women undergoing IVF. They found that EPA levels were significantly higher in pregnant than non-pregnant women (P = 0.006), and following adjustment for age and body mass index (BMI), total fatty acids was correlated with highquality oocytes.…”
Section: Omega-3 Pufas In Assisted Reproductive Technologiesmentioning
confidence: 94%
“…No correlation between omega-3 PUFA index and IVF outcomes. Mirabi et al, 2017), Iran 105 Serum level of fatty acid Yes EPA serum level was significantly higher in pregnant women. Chiu et al, 2018, USA 100 Serum level of fatty acid on days 3-9 of stimulation Yes High levels of total omega-3 PUFAs and EPA are associated with higher probability of pregnancy and live birth.…”
Section: Yesmentioning
confidence: 97%
See 2 more Smart Citations